Microgrid technology and engineering application - Li, Fusheng; Li, Ruisheng; Zhou, Fengquan (London Academic Press, 2016)
This book is based on the authors’ research and microgrid projects since 2009, and is the most up-to-date resource on the development of microgrid technologies. In addition to basic facility and network design concepts, it covers related subjects including power supply programming and energy optimization, which means it can serve as a single volume reference to the complete microgrid system implementation.--Provided by publisher.
Chapter 1: Overview of microgrid -- Chapter 2: Composition and classification of the microgrid -- Chapter 3: Microgrid and distributed generation -- Chapter 4: Control and operation of the microgrid -- Chapter 5: Protection of the microgrid -- Chapter 6: Monitoring and energy management of the microgrid -- Chapter 7: Communication of the microgrid -- Chapter 8: Earthing of a microgrid -- Chapter 9: Harmonic control of the microgrid -- Chapter 10: Related standards and specifications -- Chapter 11: A practical case -- Appendix: List of abbreviations -- References -- Index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Small power production facilities; Distributed generation of electric power; Smart power grids; Electronic books